Salmonella Typhimurium biofilm disruption by a human antibody that binds a pan-amyloid epitope on curli - Sarah A. Tursi (Nature Portfolio, 2020)
Curli amyloid fibers are important components of bacterial biofilms formed by E. coli and Salmonella. Here, Tursi et al. show that a human monoclonal antibody with pan-amyloid binding activity can disrupt biofilms formed by Salmonella Typhimurium in vitro and in vivo.